(untitled) (Revista de Crítica Literaria Latinoamericana, 2023)
This paper explores the narration of Héctor Llaitul, a historical reference of the Coordinadora Arauco-Malleco, an organization of armed resistance associated with the Mapuche people of southern Chile, regarding the historical facts exposed in La Araucana by Alonso de Ercilla. I establish a relationship between that epic text and Llaitul’s principles and thoughts about the military and weichafe ethics in reference to Lautaro (Leftraru). There is an analysis about contradictions and political and identity complexities that Llaitul, along with Jorge Arrate, his co-author in Weichan who interviews him in prison, finds regarding the Araucanian-Mapuche legacy that is declared in the Chilean republican tradition and that actually comes from La Araucana.